2020
DOI: 10.1088/1755-1315/530/1/012040
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of phytoplankton from polyculture milkfish and white shrimp vanname pond culture waters, Pekalongan region

Abstract: The objectives to study the effect of Biodiversity of Phytoplankton on the productivity in Polyculture Milkfish and White shrimp vanname Pond Culture waters, Kandang Panjang Pekalongan Region, Centre of Java. Methodology The sampling have tried station T1,T2,T3,T4 were in pond culture of polyculture waters to identify a phyto planton in polyculture pond Kandang Panjang waters. The sampling was carryout between Pebruary to Mei 2018. The result study showed that the value of the diversity indices in T1 treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Plankton diversity and abundance support polyculture productivity, as reported from several regions (Soedibya, 2013;Mutia et al, 2018;Kusuma et al, 2019). Some studies reported the support of natural food in the polyculture pond of Nile Tilapia, Oreochromis niloticus (Soedibya, 2013;Ahsan et al, 2014;Ekasari et al, 2015;Kusuma et al, 2019;Samidjan et al, 2020). Also, other studies found similar data in Milkfish Chanos chanos (Sihombing et al, 2017;Muyot et al, 2018).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Plankton diversity and abundance support polyculture productivity, as reported from several regions (Soedibya, 2013;Mutia et al, 2018;Kusuma et al, 2019). Some studies reported the support of natural food in the polyculture pond of Nile Tilapia, Oreochromis niloticus (Soedibya, 2013;Ahsan et al, 2014;Ekasari et al, 2015;Kusuma et al, 2019;Samidjan et al, 2020). Also, other studies found similar data in Milkfish Chanos chanos (Sihombing et al, 2017;Muyot et al, 2018).…”
Section: Introductionmentioning
confidence: 87%
“…The ecological benefits of Saline Nile Tilapia have been used to develop brackish water aquaculture and it has been polycultured with various fisheries products (Soedibya, 2013;Ekasari et al, 2015;Muyot et al, 2018). Therefore, the intensive polyculture of saline Nile Tilapia and Milkfish, Chanos chanos has been carried out in ponds (An and Anh, 2020;Samidjan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In intensive ponds with a phytoplankton diversity index (H') of around 1.95 while in traditional ponds around 2.17 [14] The dominance index value in intensive ponds is 0.18 and in traditional ponds is 0.15; the high abundance of phytoplankton will disturb and can threaten the failure of Vanname shrimp production in intensive ponds [15]. Milkfish can be used as a biofilter in inlet and outlet maintenance plots, which can control phytoplankton populations and can improve the survival of Vananame shrimp in ponds [16]. Phytoplankton blooms are influenced by nutrient inputs from the external environment, while internal interactions between phytoplankton and zooplankton are still difficult to predict [17].…”
Section: Plankton Compositionmentioning
confidence: 99%